PENGARUH KEBANGKRUTAN MODEL ALTMAN Z – SCORE TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BEI PERIODE 2014 - 2016 - Noviarti (Jurnal Manajemen, 2017)
The purpose of this research is to figure out if there is the effect of Altman Z-Score bankruptcy analysis on stock prices at Manufacturing companies listed on the Stock Exchange in the period 2014-2016. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014-2016 which is 142 companies. Research sample is 42 companies with Purposive Sampling as sampling technique. Hypothesis testing in this research using simple linear regression analysis to test the effect of Z-Score on stock price and multiple linear regression analysis to test variable Altman Z-Score to Stock Price. The results of this study show the partial Z-Score only significant effect on Price Stock. The results also show partially that the variable Altman Z-Socre only Market Value Of Equity To book Value Liabilities significantly influence the Price Stock. And the results of research also show that variable Altman Z-Score is Working Capital To Total Asset, Retained Earning To Total Asset, Earning Before Interest And Taxes To Total Asset, Market Value Of Equity To Book Value Liabilities and Sales To Total Asset simultaneously have an effect on Price Stock.